Criminal behavior in the physical element of crimes of assault on peaceful demonstrators Iraqi and Egyptian - Abdul Jalil Ghadban Mahdi; Gholam Ali Qasimi (Journal of College of Education, 2024)
Any citizen in society has the right to express an opinion about his situation or a specific issue related to aspects related to the social or economic situation which he can express through peaceful demonstration in accordance with the rules laws and legislation in force as long as it does not harm the security of the country and is far from provoking strife riots chaos and protecting property public and private taking into account the freedom of others and maintaining adherence to the rules and principle of freedom and rights The current aims to identify the material element in the crimes related to assaulting peace ful demonstraators in the laws and Egypt on the criminal act. Ther are many crimes committed against peacefull demonstratators including the crime of murder the crime of siliver assault the crime of disability the crime silver assaulte the crime of harmand the crime of threat . The law does not punish mere criminal intention and thoughts unless they take on an extenrnal appearance that indicates them and conformsto the criminal text. Therefore a criminal incident requires criminal behavior to aachieve it. Next comes examining the responsibility of its perpetrator and determining the Given the importanance of behavior Often for the sake of dominance whate is meant by the material element is thisbehavior in itseif even though it is not sufficient to determine the crime beacause the legislator stipulated specific result.Thererfore the materialelements in the material element are in the material element are the behavior that determines the criminal incident and it is a common element among all crimes . Thereforeit necessary to research the material element of the crimes of assaulting peaceful demonstrators.